Up-regulation of hepatic fatty acid transporters and inhibition/down-regulation of hepatic OCTN2 contribute to olanzapine-induced liver steatosis. (November 2019) - Jiang, Ting; Zhang, Yingqiong; Bai, Mengru; Li, Ping; Wang, Wei; Chen, Mingyang; Ma, Zhiyuan; Zeng, Su; Zhou, Hui; Jiang, Huidi
Highlights: Olanzapine up-regulates hepatic FABP1 and FATP2 expression in livers of female mice. Olanzapine down-regulates OCTN2 expression in livers of male mice. Olanzapine inhibits hepatic OCTN2 activity and decreases hepatic L-carnitine level. L-carnitine supplementation attenuates olanzapine-induced simple steatosis. Abstract: Olanzapine, a representative of antipsychotics, is a first-line drug for treatment of schizophrenia. However, olanzapine-induced liver steatosis limits its clinical utilization. This study is to explore the mechanism of liver steatosis induced by olanzapine based on the regulation of transporters involved in uptake and oxidation of fatty acids. Our results revealed that 12-week oral administration of olanzapine increased hepatic triglyceride(TG), caused liver steatosis. Our further studies showed that the expression of fatty acid transporter 2(FATP2) and fatty acid binding protein 1(FABP1) were up-regulated in liver of female mice after 12-week olanzapine exposure, as well as in primary mouse hepatocytes treated with olanzapine. Olanzapine treatment also reduced hepatic β-hydroxybutyrate level (indicator of fatty acid β-oxidation), meanwhile, the L-carnitine (L-Car) concentration in liver of olanzapine group was significantly lower than that in control group. Further study demonstrated that both mRNA and protein expression of hepatic OCTN2 (carnitine/organic cation transporter 2) were obviously down-regulated in male mice after 12-week olanzapine treatment. Also, olanzapine markedly inhibited L-Car uptake in MDCK-hOCTN2 cells (1.06 μM of IC50 ), HepG2 cells and primary mouse hepatocytes. Supplementation of L-Car attenuated hepatic TG rise and improved simple steatosis in olanzapine treatment mice. Taken together, up-regulation of FATP2/FABP1 and down-regulation/inhibition of hepatic OCTN2 probably contribute to olanzapine-induced liver steatosis. Supplementation of L-Car is a promising strategy to attenuate olanzapine-induced simple steatosis.